The Functional Role of the 3′ Untranslated Region and Poly(A) Tail of Duck Hepatitis A Virus Type 1 in Viral Replication and Regulation of IRES-Mediated Translation - Chen, Jun-Hao; Zhang, Rui-Hua; Lin, Shao-Li; Li, Peng-Fei; Lan, Jing-Jing; Song, Sha-Sha; Gao, Ji-Ming; Wang, Yu; Xie, Zhi-Jing; Li, Fu-Chang; Jiang, Shi-Jin (Frontiers in Microbiology, 2018)
The duck hepatitis A virus type 1 (DHAV-1) is a member of Picornaviridae family, the genome of the virus contains a 5′ untranslated region (5′ UTR), a large open reading frame that encodes a polyprotein precursor and a 3′ UTR followed by a poly(A) tail. The translation initiation of virus proteins depends on the internal ribosome-entry site (IRES) element within the 5′ UTR. So far, little information is known about the role of the 3′ UTR and poly(A) tail during the virus proliferation. In this study, the function of the 3′ UTR and poly(A) tail of DHAV-1 in viral replication and IRES-mediated translation was investigated. The results showed that both 3′ UTR and poly(A) tail are important for maintaining viral genome RNA stability and viral genome replication. During DHAV-1 proliferation, at least 20 adenines were required for the optimal genome replication and the virus replication could be severely impaired when the poly (A) tail was curtailed to 10 adenines. In addition to facilitating viral genome replication, the presence of 3′ UTR and poly(A) tail significantly enhance IRES-mediated translation efficiency. Furthermore, 3′ UTR or poly(A) tail could function as an individual element to enhance the DHAV-1 IRES-mediated translation, during which process, the 3′ UTR exerts a greater initiation efficiency than the poly(A)25 tail.